Pengaruh Net Interest Margin, Non-Performing Loan, Suku Bunga, dan Nilai Tukar terhadap Harga Saham Perbankan (Periode 2020-2024) - Richie Richie; Muliawati Muliawati (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
The rapid increase in Indonesian capital market investors, reaching 14.8 million by the end of 2024, reflects rising financial literacy and public interest in investment. However, global crises and domestic policy shifts, such as the COVID-19 pandemic, geopolitical conflicts, and credit write-off policies, have created volatility in the banking sector and pressured stock prices. This study aims to examine the effect of net interest margin (NIM), non-performing loans (NPL), interest rates, and exchange rates on the stock prices of banking companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. Using a hypothetico-deductive and causal research design, the study employs secondary data from financial reports and Bank Indonesia, with purposive sampling of 24 banks. Multiple linear regression was applied with classical assumption tests. The results show that NIM has a significant positive effect, while NPL has a significant negative effect on stock prices. Conversely, interest rates and exchange rates do not exert significant influence. Simultaneously, all four variables significantly affect stock prices, though the contribution is relatively modest (8.3%). These findings suggest that investors should prioritize NIM and NPL when evaluating investment decisions. Academically, the study contributes to the debate on the role of profitability and credit risk as key drivers of stock performance in emerging markets.